A cupric reducing antioxidant capacity assay coupled to thin‑layer chromatography - Micheloni, Oscar Bernardo (2024)
The use of natural antioxidant extracts in food processing is a growing trend, aligning with increasing ecological awareness and meeting consumer demands for safe, high-quality food products. Plants play a significant role in human health owing, in part, to their antioxidant properties. Analyzing the antioxidant properties of complex natural extracts requires simple, cost-effective tools. The cupric reducing antioxidant capacity (CUPRAC) method is a reference for evaluating plant extract antioxidant capacity. A new CUPRAC thin-layer chromatography (TLC) assay, involving agarose immobilized reagents, was developed and applied to investigate the antioxidant properties of Solanum sisymbriifolium Lam., Sinapis arvensis L., and Cichorium intybus L. The best results were obtained by pouring a solution containing agarose, copper(II) chloride, 2,2-azino-bis[3-ethylbenzothiazoline-6-sulfonic acid] (ABTS), and neocuproine in ammonium acetate buffer over a TLC plate at 40 °C (with final concentrations of 0.485 µmoles/cm2 copper(II) chloride and 0.368 µmoles/cm2 neocuproine) and incubating for 15 min. The limits of detection and quantification for Trolox® were 0.09 and 0.30 µg, respectively.